PENGARUH DISIPLIN BELAJAR TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS VII DI MTs BAHRUL ULUM - Nur Azizah; welven aida; Hardianto (Program Studi Pendidikan IPS, 2023)
The purpose of this study was to determine the effect of learning discipline on learning outcomes in social studies class VII students at MTs Bahrul Ulum. This research is a quantitative research with the regression method, the population in this study amounted to 102 class VII students and the sample technique used in this study was total sampling and the data analysis technique used was simple linear regression analysis. The results based on the hypothesis testing that has been done, it is obtained that the tcount is 7,518 > ttable 1,660 at a significance level of 5%, meaning that there is a positive and significant influence between learning discipline on learning outcomes in social studies class VII students at MTs Bahrul Ulum in Pasir Utama Village. Based on the coefficient of determination which states that the value influences learning discipline on learning outcomes in social studies subjects with a contribution value of 36.1%, while the remaining 63.9% is a contribution from other variables not discussed in this study.